2014
DOI: 10.1007/s13277-014-2466-z
|View full text |Cite
|
Sign up to set email alerts
|

LEF1 regulates glioblastoma cell proliferation, migration, invasion, and cancer stem-like cell self-renewal

Abstract: Glioblastoma multiforme (GBM; WHO grade IV) is one of the most common primary tumors of the central nervous system. This disease remains one of the incurable human malignancies because the molecular mechanism driving the GBM development and recurrence is still largely unknown. Here, we show that knockdown of lymphocyte enhancer factor-1 (LEF1), a major transcription factor of Wnt pathway, inhibits U251 cell migration, invasion, and proliferation. Furthermore, downregulation of LEF1 expression inhibits the self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 27 publications
2
41
0
2
Order By: Relevance
“…A previous study stated that Wnt caused elevated LEF1 expression in a β-catenin-independent and LEF1-dependent manner [40], which supports our finding of β-catenin-independent LEF1 repression by mangiferin in HCC cells. LEF1 related signalling is a multi-targeted regulatory mechanism in which the aberrant activation of LEF1 results in cancer development by promoting processes such as invasion, proliferation, and self-renewal of cancer cells [28,41,42]. Our molecular finding that mangiferin represses LEF1 target genes accords with these previous studies, especially given our cellular finding mangiferin restricted HCC cell proliferation, migration, and chemotactic properties.…”
Section: Discussionsupporting
confidence: 88%
“…A previous study stated that Wnt caused elevated LEF1 expression in a β-catenin-independent and LEF1-dependent manner [40], which supports our finding of β-catenin-independent LEF1 repression by mangiferin in HCC cells. LEF1 related signalling is a multi-targeted regulatory mechanism in which the aberrant activation of LEF1 results in cancer development by promoting processes such as invasion, proliferation, and self-renewal of cancer cells [28,41,42]. Our molecular finding that mangiferin represses LEF1 target genes accords with these previous studies, especially given our cellular finding mangiferin restricted HCC cell proliferation, migration, and chemotactic properties.…”
Section: Discussionsupporting
confidence: 88%
“…We detected downregulation of PCNA in 5637 and UMUC-3 cells knocked down for HMGB3. MMP2, which can degrade collagen IV, the major extracellular matrix component of the basement membrane, is implicated in nonphysiological tissue invasion and migration [23]. We found that the protein level of MMP2 was decreased in HMGB3-silenced 5637 and UMUC-3 cells.…”
Section: Discussionmentioning
confidence: 68%
“…3,68 Although most studies have addressed canonical WNT signaling, several studies have indicated the involvement of both canonical and non-canonical WNT signaling. 22,83 WNT SIGNALING IN GBM INVASION Tumor metastasis is a major factor contributing to tumorassociated death. Epithelial-mesenchymal transition (EMT) is a critical process that enables cancer cells of epithelial origin to metastasize to distal organs.…”
Section: Wnt Signaling In Gbm Stem Cells (Gscs)mentioning
confidence: 99%